HUBUNGAN KEBIASAAN MENGKONSUMSI MAKANAN DAN MINUMAN BERKARBONAT DAN BERKAFEEIN DENGAN KEPADATAN TULANG REMAJA (STUDI DI SMAN 3 SEMARANG) - Wulandari Meikawati (Universitas Muhammadiyah Semarang, 2008)
BACKGROAND: Calcium reqquirement during adolescence is higher than the other period of life.Caffeinated ond carbonited dink are one ofseveral factors that influence calcium icretionfrom urine.OBJECTIWS: Tofind out correlation between cffiinated and carbonated drinkconsumptionwith adolescents, bone density.MEIWOD: The method of this study wcts survey with a cross sectional approach. The population of study were of S!AN i Semarang student in grade l" and 4 ,rt!r, subjects *"r" 7*n througi i ,i^pt